Therapeutic Myostatin Inhibitors in Sarcopenia – A Review of Their Effects on Muscle Mass, Strength, and Function - Okliński, Bartosz; Skrzypek, Jakub; Fidut, Natalia; Szyprowski, Karol; Zioło, Kamila; Zarzycka, Weronika; Kisielewski, Maciej; Wawerska, Julia; Wrzosek, Weronika; Zugaj, Mateusz (Quality in Sport, 2026)
Background. Sarcopenia is an age-related syndrome characterized by progressive loss of skeletal muscle mass, strength, and physical performance, leading to increased risks of disability, falls, hospitalization, and mortality. Myostatin, a negative regulator of muscle growth, has emerged as a potential therapeutic target in sarcopenia. Aim. The aim of this review was to evaluate the current evidence regarding the use of myostatin inhibitors in sarcopenia, with particular emphasis on their effects on muscle mass, strength, and physical function. Material and methods. A narrative review of the literature was conducted, including experimental studies, randomized controlled trials, systematic reviews, and meta-analyses investigating myostatin inhibition in sarcopenia and related muscle-wasting conditions. Results. Available evidence indicates that myostatin inhibitors increase lean body mass and promote skeletal muscle hypertrophy. Clinical studies, particularly those involving bimagrumab, demonstrated significant gains in muscle volume and lean mass. However, improvements in muscle strength and physical performance were generally limited and not always proportional to increases in muscle mass. Current evidence is constrained by heterogeneous study populations and short follow-up periods. Conclusions. Myostatin inhibitors may represent a useful pharmacological strategy for increasing muscle mass in sarcopenia. Nevertheless, their effects on functional outcomes remain uncertain. Further studies are needed to assess long-term clinical benefits and the effectiveness of combining pharmacological treatment with exercise and nutritional interventions.